1976
DOI: 10.1177/001100007600600105
|View full text |Cite
|
Sign up to set email alerts
|

Periods in the Adult Development of Men: Ages 18 to 45

Abstract: This is a preliminary statement of a theory of psychosocial periods in the development of men from the end of adolescence to the middle 40s. The theory has emerged from a study of 40 men currently in the mid-life decade (age 35-45). The method was biographical: through a series of interviews we constructed the adult life course of each man and looked for a sequential order underlying the highly diverse, unique individual biographies. (a) The first period, Leaving the Family, is a bridge between adolescent life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0
7

Year Published

1977
1977
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 2 publications
2
47
0
7
Order By: Relevance
“…Table 1 presents the demographic information of the subjects in terms of their gender and marital status. ------------------------------------------------------------------------------------------------------------------------ Table 2 shows the classification of age into nine categories based on Levinson's Adult Life Course Theory (Levinson, Darrow, Klein, Levinson & McKee, 1976). In terms of age the respondents of age 28-32 dominate the sample size with 36.8%, followed by 22-27 years age group (27.4%) and 33-39 years age group (13.2%).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 presents the demographic information of the subjects in terms of their gender and marital status. ------------------------------------------------------------------------------------------------------------------------ Table 2 shows the classification of age into nine categories based on Levinson's Adult Life Course Theory (Levinson, Darrow, Klein, Levinson & McKee, 1976). In terms of age the respondents of age 28-32 dominate the sample size with 36.8%, followed by 22-27 years age group (27.4%) and 33-39 years age group (13.2%).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies (Hedlund & Ebersole, 1983;Kittrell, 1998;Levinson, 1996;Minter & Samuels, 1998) supporting this finding are available in the relevant literature. Levinson et al (1976) found in a study with males in early adulthood that a peaceful life style was in the first plan among their dreams. Levinson (1996), in a study with females in early adulthood, found that the future projection shaping the individual life structure was an important factor in one's professional life.…”
Section: Self-representationmentioning
confidence: 99%
“…Another theorist importantly considering adulthood in the relevant literature is Levinson. Levinson (1977;1986) and Levinson, Darrow, Klein, Levinson, and McKee (1976), explaining human development within a course of life, constructed the theory of individual life structure upon studying males in their mid-adulthood. Levinson developed his theory later (1987; adding early-adulthood females in his research (Levinson, 1996).…”
mentioning
confidence: 99%
“…Les recherches de Levinson (1976Levinson ( , 1977Levinson ( , 1978aLevinson ( , 1978b) s'articulent essentiellement autour de la découverte que la vie est, selon le langage métaphorique de l'auteur, un voyage qui s'effectue selon un itinéraire précis, bien qu'il ne soit pas exclu que de nombreuses variations culturelles,et personnelles puissent venir rompre la monotonie de ce voyage. Or ce voyage, lorsque l'on en expose le tracé, laisse apparaître une structure dont l'organisation et la séquence sont, dans le cours de la vie des individus soumis à l'expérimentation, d'une ressemblance frappante.…”
Section: A) Les Recherches De Daniel Levinsonunclassified